The Effect of Working Capital, Leverage, and Firm Size towards Corporate Performance with Liquidity as Moderating Variables - Adam Firman Rizqi; Wiwi Idawati (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
The purpose of this research to analyse the effect of working capital, leverage, firm size and liquidity on corporate performance, with liquidity as a moderating variable. Samples in this research uses the 29 companies listed on IDX are in the category LQ45 period February 2013 - February 2016. The analytical tool used in this research is multiple linear regression models with path analysis. These results indicate that working capital positive effect on corporate performance, firm size negative effect on corporate performance. Leverage and Liquidity are no effect on corporate performance. Liquidity as a moderating variable indicate strengthen the effect of working capital while liquidity weakens the leverage effect on corporate performance.